THE SEVERITY OF THE CLINICAL EFFECT AND THE LEVEL OF PAIN SYNDROME IN PATIENTS AFTER ENDOVASAL LASER OBLITERATION AND COMBINED PHLEBECTOMY - Черных, Константин Петрович; Кубачев, Кубач Гаджимагомедович; Казанцев, Антон Николаевич; Черных, Александр Петрович; Заркуа, Нонна Энриковна; Багдавадзе, Г. Ш. (Medicine in Kuzbass, 2020)
Purpose – assess the dynamics of clinical symptoms and the severity of pain in patients with lower limb varicose veins (VBHK) after endovasal laser obliteration (EVLO) and combined phlebectomy (CF).Materials and methods. The survey evaluated the hospital results of treatment of 408 patients. All patients were divided into two groups: Group 1 – endovasal laser obliteration (EVLO) was performed on patients (n = 257, 63 %); Group 2 – patients underwent combined phlebectomy (CF) (n = 151, 37 %). Patient recruitment was performed on an outpatient basis. Based on the results of the examination and examinations, a diagnosis was made on the scale of the CEAP, on the basis of which a conclusion was drawn up about the need for surgical correction. The severity of symptomatic dynamics in the postoperative period was assessed according to the VCSS scale. The intensity of the pain was determined for seven days after surgery according to the visual analogue scale (Visual Analog Scale).Results. On the 7th day after the treatment, rekazalization according to ultrasound in both groups was not observed. The severity of pain among patients with EVLO during the first 4 postoperative days was significantly less than in patients with CF. Thus, the average pain index for 10 days in the second group was 0.8 points higher than the index of the first group (p = 0.045). According to the VCSS scale, the KF group was five times superior to EVLO.Conclusion. Thus, the main effect of the treatment was obtained equally well by the results of the use of both EVLO and CF. However, EVLO, due to its lower trauma, has shown its advantages relative to CF in the form of a minimum rehabilitation period and the rare need to use non-steroidal anti-inflammatory drugs.
Keywords: chronic venous insufficiency of the lower extremities; endovasal laser obliteration; combined phlebectomy; hospital period; pain syndrome